Affective, Interactive and Cognitive Methods for E-Learning Design
DOI: 10.4018/978-1-60566-940-3.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Education

Abstract: Virtual Reality is implemented by a combination of technologies that are used in order to visualize and provide interaction with a virtual environment. These environments often depict three-dimensional space which may be realistic or imaginary, macroscopic or microscopic and based on realistic physical laws of dynamics, or on imaginary dynamics. The multitude of scenarios that VR may be used to depict make it broadly applicable to the many areas in education. A key feature of VR is that it allows multi-sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
6

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 13 publications
1
55
0
6
Order By: Relevance
“…In case of education purposes, virtual platforms usually simulate the classroom or the laboratory. However, sometimes, they provide a safe environment to test scenarios that would be too difficult or dangerous to perform in real life [37]. In this paper, we propose a VR applications taxonomy based on the learning outcomes and objectives according to three categories [38]: remembering and understanding, using acquired knowledge in typical situation and using acquired knowledge in a challenging situation.…”
Section: Types Of Virtual Educational Environmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In case of education purposes, virtual platforms usually simulate the classroom or the laboratory. However, sometimes, they provide a safe environment to test scenarios that would be too difficult or dangerous to perform in real life [37]. In this paper, we propose a VR applications taxonomy based on the learning outcomes and objectives according to three categories [38]: remembering and understanding, using acquired knowledge in typical situation and using acquired knowledge in a challenging situation.…”
Section: Types Of Virtual Educational Environmentsmentioning
confidence: 99%
“…The majority of modern existing VR solutions are based on HMDs, which provide a total immersion through 3D virtual environment imitating the reality. According to [37], one of the key issues that should be addressed in the very near feature is the lack of visual realism and realism of the dynamics and interaction. It can be concluded that existing techniques used to generate VR graphics and displaying technology are quite limited.…”
Section: Challenges and Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…By using VR and 3D modelling in the process of learning at vocational studies, students are provided numerous opportunities that cannot provide them with a classical form of a lecture. By researching these areas and technologies, it can be concluded that VR and 3D modelling trends are rapidly expanding and affecting all spheres of life [3,4,6]. Virtual reality was primarily used as a technology to improve computer gaming experience, but today it is developing intensively in other directions too.…”
Section: Usage Of Virtual Reality and 3d Modelling In The Learning Prmentioning
confidence: 99%